If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 6 = -1 + -3c Reorder the terms: 6 + 2c = -1 + -3c Solving 6 + 2c = -1 + -3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3c' to each side of the equation. 6 + 2c + 3c = -1 + -3c + 3c Combine like terms: 2c + 3c = 5c 6 + 5c = -1 + -3c + 3c Combine like terms: -3c + 3c = 0 6 + 5c = -1 + 0 6 + 5c = -1 Add '-6' to each side of the equation. 6 + -6 + 5c = -1 + -6 Combine like terms: 6 + -6 = 0 0 + 5c = -1 + -6 5c = -1 + -6 Combine like terms: -1 + -6 = -7 5c = -7 Divide each side by '5'. c = -1.4 Simplifying c = -1.4
| 70+30=2x | | 3n^2+6n-24=0 | | 5m^2-50m+125=0 | | 6-(1/3)x=2x-3 | | 5(a-8)+14=3(a-6) | | 5m+9=4 | | 5-2x=x+6 | | -6x-3(2x-18)=186 | | -50=5x+4(-3x-2) | | 5x*3y= | | a/2+b/2=c/2 | | 4p^2-4p-48=0 | | -8-9=-3(d+3)-5d | | 2(3x-4)=2(21x+16) | | -5x+2(-2x-11)=-76 | | 2x+3.4=8 | | 2x(3x+1)=28 | | xy+30y-30=0 | | 5x^(1/3)-x^(2/3)-54=0 | | -8r-7=24 | | 20(-1/2) | | 1/5(2x+9)=2(1-2x)+13 | | 190=-7x-5(5x-6) | | -8(1+6n)=-344 | | 1/15r=41/2 | | -3x+7(x+4)=68 | | (-7/11)(-11) | | -1/6+(-5/8) | | 108=-5x-3(-5x-16) | | -15-4=9-8x | | 2b^2-6b-20=0 | | 7(1+2n)=119 |